Family nursing care for infants in improving home-based infant care - Najwatul Syiffani; Yuni Arnita (Indonesian Journal of Health Science, 2026)
Infant growth and development require close attention from parents, as this stage is highly vulnerable to health problems, particularly those related to nutritional adequacy and disease. Inappropriate complementary feeding (MP-ASI) and incomplete basic immunization may negatively affect infants’ growth, development, and health status. This final scientific paper aimed to describe family nursing care for issues related to complementary feeding and incomplete basic immunization. Based on the assessment conducted on 18 December 2025, priority nursing diagnoses identified in the family were ineffective family health management related to inadequate understanding of complementary feeding and ineffective family health management related to immunization behavior. Nursing care planning was developed based on the five family health tasks. Interventions included health education on complementary feeding concepts, demonstration of balanced nutrition menus (four-star menu) on a plate, provision of daily four-star menu examples, and explanation of healthcare services for monitoring infant growth and development. In addition, education on the importance of complete immunization was provided, including management using flashcards and educational videos illustrating differences between immunized and non-immunized children, as well as demonstration of the management of adverse events following immunization (AEFI). Modifications were also implemented by providing a scheduled roster aligned with age-appropriate immunization schedules as a reminder. Evaluation results showed improvements in the family’s knowledge, attitudes, and motivation in meeting the infant’s health needs. This nursing care is expected to serve as a reference for community health center nurses in delivering health education to families to optimize infant health outcomes.